Modelado de canales iónicos como procesos de Markov - Ávila-Pozos, Roberto; González-Vélez, Virginia; Rafael Godínez-Fernández, J. (Revista Mexicana de Ingenieria Biomedica, 2006)
We review basic concepts of Markov processes as they are discrete state models with stochastic transitions. We emphasize how to calculate transition probabilities between states and their random variables. Through this paper, we discuss how this concept could be applied to support a mathematical modeling of ionic channels. Channels have several conformational states and they skip from one to another in a non-deterministic fashion, so these techniques may be useful to understand channel behavior. Finally, we detail the mathematical analysis for a two-state model and include some simulations obtained from it. The unitary currents simulated are important since they can be added to obtain the whole-cell macroscopic current, found in excitable cells.